2015
DOI: 10.1073/pnas.1424792112
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of CD39 on regulatory T cells as a biomarker for resistance to methotrexate therapy in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease characterized by joint destruction and severe morbidity. Methotrexate (MTX) is the standard first-line therapy of RA. However, about 40% of RA patients are unresponsive to MTX treatment. Regulatory T cells (Tregs, CD4 + CD25 + FoxP3 + ) are thought to play an important role in attenuating RA. To investigate the role of Tregs in MTX resistance, we recruited 122 RA patients (53 responsive, R-MTX; 69 unresponsive, UR-MTX) and 33 healthy controls. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 35 publications
(34 reference statements)
6
99
3
3
Order By: Relevance
“…CD73 is required for low-dose MTX-induced immunomodulatory effect observed in the air pouch model 5 6. CD39, the directly upstream ectoenzyme of CD73, has also been shown to influence clinical response to MTX in patients with RA 25. The interaction between MTX and BAFF can be explained, at least partly, by the increase of CD73 expression on B cells from BAFFtg mice.…”
Section: Discussionmentioning
confidence: 99%
“…CD73 is required for low-dose MTX-induced immunomodulatory effect observed in the air pouch model 5 6. CD39, the directly upstream ectoenzyme of CD73, has also been shown to influence clinical response to MTX in patients with RA 25. The interaction between MTX and BAFF can be explained, at least partly, by the increase of CD73 expression on B cells from BAFFtg mice.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory effects of CD39 + Tregs on experimental RA and RA patients subjected to anti-IL-6 receptor (IL-6R) treatment were also been shown by flow cytometric analysis of peripheral blood. 77 Low peripheral expression levels of CD39 have also been proposed as biomarkers for RA in patients 78 , and CD39-expressing Tr1 cells proposed as potential therapy against arthritis. 79 In patients suffering from inflammatory bowel disease, peripheral Th17 cells expressing CD39 had enhanced in vitro immunosuppressive effects.…”
Section: Murine Cd39 Expressing T Cells As Enhanced Immunomodulation mentioning
confidence: 99%
“…However, a significant percentage of rheumatoid arthritis patients are resistant to MTX treatment. Peres et al [26] found that MTX unresponsiveness in rheumatoid arthritis patients was associated with low expression of CD39 on Treg cells and the deceased suppressive activity of Treg cells through reduced adenosine production. These data suggested that low expression of CD39 on Treg cells could be a biomarker for identifying MTX-resistance rheumatoid arthritis patients.…”
Section: Adenosine Pathway Changes In Human Autoimmune Diseasesmentioning
confidence: 99%